2017
DOI: 10.1111/are.13307
|View full text |Cite
|
Sign up to set email alerts
|

Short-term starvation in silver pomfret (Pampus argenteus): molecular effects on lipid mobilization and utilization

Abstract: increased lipid mobilization and utilization possibly through activation of lipolysis-related genes (HSL and ATGL), lipid uptake-related genes (LPL, CD36, FATP1 and FABPpm) and PPARs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
6
21
0
Order By: Relevance
“…In mammals, FABPpm has been identified as a fatty acid transporter in skeletal muscle (Clarke et al, ). In fish, a mammalian‐type FABPpm is also reported in trout and silver pomfret (Liao et al, ; Richards et al, ). However, unlike in mammals, the structure of FABPpm in trout may differ between white muscle and red muscle (Richards et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In mammals, FABPpm has been identified as a fatty acid transporter in skeletal muscle (Clarke et al, ). In fish, a mammalian‐type FABPpm is also reported in trout and silver pomfret (Liao et al, ; Richards et al, ). However, unlike in mammals, the structure of FABPpm in trout may differ between white muscle and red muscle (Richards et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…During postprandial period (0–12 hr after feeding), an increase in fatty acid transporters could be responsible for the enhanced uptake of dietary fatty acids (Sánchez‐Gurmaches et al, ), in accord with the increased FA transporters expression observed (including liver CD36, FABPpm‐a, FABPpm‐b, FATP1‐a and FATP6, intestine CD36, FABPpm‐a and FABPpm‐b, and muscle CD36 and FATP1‐b). During food deprivation, fatty acids derived from lipid mobilization are usually transported into muscle to support an increase in fatty acid oxidation in starved fish (Liao et al, ). In the present study, it seemed that an increase in expressions of fatty acid transporters (including liver CD36, FABPpm‐a, FABPpm‐b and FATP1‐a, intestine FABPpm‐a, FABPpm‐b, FATP4 and FATP6, and muscle FATP1‐b, FATP4 and FATP6) played a critical role in coordinating the energy supply to other tissues in starved zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous aquaculture studies on P. argenteus exposed to a transportation stressor (Zhang et al, 2017) showed that the fish panicked, leading to injury or even death. Furthermore, the fish kept swimming under normal conditions and exhibited relatively low tolerance to starvation (Liao et al, 2017). Therefore, low growth rates and high mortality have been found to be associated with the culture practices for P. argenteus.…”
Section: Introductionmentioning
confidence: 99%